Paroxysmal nocturnal hemoglobinuria: a single Spanish center's experience over the last 40 yr. (13th May 2014) - Muñoz‐Linares, Cristina; Ojeda, Emilio; Forés, Rafael; Pastrana, Miguel; Cabero, Martín; Morillo, Daniel; Bautista, Guiomar; Baños, Isolina; Monteserín, Carmen; Bravo, Pilar; Jaro, Esther; Cedena, Teresa; et al.
Abstract Paroxysmal nocturnal hemoglobinuria (PNH) is a rare clonal disease. To date, many reviews and series have been described. We report the experience of our center by presenting a review of 56 PNH patient cases with an average age at diagnosis of 38 yr and follow‐ups beginning at approximately 40 yr; the median survival rate was 11 yr. The average clonal size upon diagnosis was 48%, presenting a variable evolution. Thrombotic episodes and cancer were five each, and the main causes of death among our patients were equal at 8.9%. Radiological study by magnetic resonance imaging is presented as a fundamental technique for estimating the deposit of iron levels in the liver and kidney, as well as in some decisive cases at the start of eculizumab therapy. Sixteen patients have been treated with eculizumab so far in our series, and being a safe drug, it provides improvement in the patients' quality of life, and the disappearance of clinical symptoms, and avoids the emergence of new thrombosis.